Spiritual Navigation : The Influence Application Religious to Life Sailors in the Era of Technology 5.0 - Sumartono, Eddy (Side: Scientific Development Journal, 2024)
Study This aiming For explore influence application religious to spiritual and mental well-being of seafarers in the era of Technology 5.0. Using method qualitative through interview deep with 15 sailors , study This find that use application digital religion such as The Bible and the Quran contribute significant to subtraction stress , mood enhancement , and strengthening personal spiritual practice . Although application This increase mental well-being , its use also raises challenge in interaction social on board , where most sailor report decline participation in communal worship . Findings This show the need balance between personal and communal spiritual practices in a very confined environment like ship . Suggestions are given For developer application religious and corporate cruise use facilitate a more spiritual experience holistic and social for sailor.